Surgical resection of locally recurrent cervical cancer: a single institutional 70 patient series. Issue 5 (1st August 2004) - Moutardier, V.; Houvenaeghel, G.; Martino, M.; Lelong, B.; Bardou, V. J.; Resbeut, M.; Delpero, J. R.
Abstract : Pelvic recurrence of cervical cancer is a life-threatening situation and only local control can provide hope for remission. The aim of this study was to evaluate the role of surgery in the treatment of cervical cancer recurrence. This retrospective study analyzed a series of 70 patients who underwent resection of cervix locoregional recurrence. Thirteen patients had palliative salvage surgery for pelvic complications. Twenty-nine resections were considered as curative. Fifty recurrences required pelvic exenterations. The hospital mortality rate was 9% and the morbidity rate was 44%. Overall 5-year actuarial survival rate was 23%. Survival was significantly higher: (a) after curative resection and (b) after centropelvic recurrence resection. Local control was obtained in 48% of the cases and 13 patients are alive with a median follow-up of 75 months. In conclusion, the results of this small and heterogen series seem to justify an attempt to resection for centropelvic recurrences whenever possible. Palliative surgery should be reserved to salvage therapy and highly selected patients.